VENA KAVA SÜPERYÖR SENDROMUNDA TANISAL CERRAHİ GİRİŞİMLER - SAYAR, Adnan; GÜLEÇ, Hakan; ÖLÇMEN, Aysun; METİN, Muzaffer; AKIN, Hasan; DEMİR, Adalet; ÖLÇMEN, Müfid (Cerrahpaşa Medical Journal, 2019)
Background.-Superior vena cava syndrome, which is easy to diagnose develops as a result of obstruction of the superior vena cava by extrinsic compression, direct invasion or thrombus. Design.-We retrospectively reviewed 10 patients in whom we detected superior vena cava syndrome and applied surgical procedures in order to clarify their etiologies. We performed 12 surgical procedures. The patients were all male with a mean age of 43,5 (1672). The surgical procedures were; 5 mediastinoscopies, 3 thoracotomies, 2 mediastinotomies, 1 sternotomy and 1 axillary biopsy. Anterior mediastinotomy was performed in two cases in addition to mediastinoscopy. Results.-The etiology was; malignancy originating from lung in 5, lymphoma in 3, and undifferentiated carcinoma in 2. In the postoperative period, we encountered complications in two patients but no mortality was detected. Conclusion.-In the superior vena cava syndrome diagnostic surgical procedures are very effective in detecting the etiology and planning an appropriate oncologic treatment in malignant lesions.